2008
DOI: 10.1007/s11999-008-0161-3
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in the Surgical Management of Developmental Dislocation of the Hip

Abstract: Although the use of ultrasound in the diagnosis and early treatment of developmental dysplasia of the hip (DDH) has reduced the number of patients diagnosed late and decreased the number of operative procedures, surgical treatment is still needed in some patients. Late cases continue to occur as a result of missing the screening examination, being normal at initial screening and missing followup. Dysplasia may persist despite appropriate nonoperative or operative treatment. Many of these patients subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 44 publications
0
30
0
4
Order By: Relevance
“…Computed tomography (CT) is useful for assessment of quality of reduction after closed or open reduction and fixation in a spica cast [51] . It is also useful in the treatment of adolescents and young adults, defining the dysplasia and allowing for better selection of the appropriate procedures, including pelvic and/or femoral osteotomies [52] . Although ionizing radiation exposure from a limited CT is low, magnetic resonance imaging (MRI) has been effectively used completely avoiding radiation exposure (Figure 1).…”
Section: Ultrasonographymentioning
confidence: 99%
See 1 more Smart Citation
“…Computed tomography (CT) is useful for assessment of quality of reduction after closed or open reduction and fixation in a spica cast [51] . It is also useful in the treatment of adolescents and young adults, defining the dysplasia and allowing for better selection of the appropriate procedures, including pelvic and/or femoral osteotomies [52] . Although ionizing radiation exposure from a limited CT is low, magnetic resonance imaging (MRI) has been effectively used completely avoiding radiation exposure (Figure 1).…”
Section: Ultrasonographymentioning
confidence: 99%
“…MRI is also useful in the assessment of labral abnormalities. Isolated labral tears are best treated with arthroscopic techniques [52] . Arthrography displays the cartilaginous anatomy of the femoral head and the acetabulum.…”
Section: Ultrasonographymentioning
confidence: 99%
“…These studies provide structural blueprints for determining alpha angles, beta angles and McKibbon indices [12]. dGEM-RIC studies can be used, when indicated, to determine the health of the cartilage [9].…”
Section: Introductionmentioning
confidence: 99%
“…Neither radiography nor CT adequately images the cartilaginous femoral head, and its position must be extrapolated from that of the proximal femoral metaphysis [2,8]. Even if the femoral head is partially ossified, its position cannot be assumed to be central.…”
Section: Introductionmentioning
confidence: 99%
“…In conservative treatment, arthrography was proposed but requires general anaesthesia [2]. Other alternative techniques such as ultrasonography remain of poor reliability [2]. Magnetic resonance imaging (MRI) has already been used in the determination of the adequacy of the surgical reduction of the dislocation of an immature hip [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%